Understanding the Costs of Care for Cystic Fibrosis: an Analysis by Age and Health State - Van Gool, K.; Norman, Richard; Delatycki, M.; Hall, J.; Massie, J. (Wiley-Blackwell Publishing, Inc., 2013)
Objectives: Cystic fibrosis (CF) is an inherited disease that requires more intensive treatments as the disease progresses. Recent medical advancements have improved survival but have also increased costs. Our lack of understanding on the relationship between disease severity and lifetime health care costs is a major impediment to the timely economic assessment of new treatments.Methods: Using data from three waves of the Australian Cystic Fibrosis Australia Data Registry, we estimate the annual costs of CF care by age and health state. We define health states on the basis of annual lung-function scores and patient’s organ transplant status. We exploit the longitudinal nature of the data to model disease progression, and we use this to estimate lifetime health care costs.Results: The mean annual health care cost for treating CF is US$15,571. Costs for patients with mild, moderate, and severe disease are US$10,151, US$25,647, and US$33,691, respectively. Lifetime health care costs are approximately US$306,332 (3.5% discount rate). The majority of costs are accounted for by hospital inpatients (58%), followed by pharmaceuticals (29%), medical services (10%), complications (2%), and diagnostic tests (1%).Conclusions: Our study is the first of its kind using the Australian Cystic Fibrosis Data Registry, and demonstrates the utility of longitudinal registry data for the purpose of economic analysis. Our results can be used as an input to future economic evaluations by providing analysts with a better understanding of the long-term cost impact when new treatments are developed.